Analisis Pembentukan Kesadaran Hukum Mahasiswa Ditinjau dari Integrasi Ilmu Hukum dan Pendidikan Agama Islam - Maslawani Maslawani; Paisal Paisal; Hajrah B (AHKAM, 2026)
Although the issue of students’ legal awareness has received attention in various previous studies, research that specifically examines the formation of legal awareness through the integration of law and Islamic education in Islamic religious higher education institutions remains relatively limited, even though this integration holds strategic potential for shaping legal awareness that is not only normative but also rooted in Islamic moral and spiritual values. This study aims to analyze the formation of students’ legal awareness in relation to the integration of law and Islamic education at Institut Agama Islam Al Amanah Jeneponto. A qualitative approach with a case study method was employed to explore in depth students’ understanding, attitudes, and legal behavior within the context of Islamic education. The participants consisted of students and lecturers selected through purposive sampling based on their relevance to the research objectives. Data were collected through in-depth interviews, observations, and document studies, and were then analyzed using an interactive analysis technique encompassing data reduction, data display, and conclusion drawing. The findings show that the formation of students’ legal awareness is influenced by their understanding of positive legal norms, the internalization of Islamic values, and learning practices that integrate cognitive, ethical, and spiritual dimensions. The integration of law and Islamic education was found to foster more reflective and value-based legal awareness among students, although challenges remain in terms of implementation and consistency in legal behavior. These findings contribute to the development of Islamic law and humanities studies by underscoring the importance of integrative approaches in legal education at Islamic higher education institutions and recommend the strengthening of curricula and integrative learning strategies to sustainably enhance students’ legal awareness.